"Letters from the Promised Land": The Ambiguous Radicalization of a Swedish Immigrant, 1928-1934 - Jean, Eva St. (Labour / Le Travail, 2004)
[This article analyzes the letters of Swedish immigrant Martin Johannson to his family in Sweden during the period 1928-34.] The letters provide glimpses into the contradictory and confusing experiences that shaped the working class during times of extreme distress, and inform on how immigrant workers in Canada perceived labour conditions and came to terms with new social circumstances. Important indications of how the depression hit the logging industry in the interior of BC more than a year before the crash of the Wall Street market in October 1929 are also conveyed. Martin felt frissons of panic as his savings dried up and he found himself competing for temporary, low-income jobs in isolated locations. Painfully aware that his failure to pay the loan instalments meant an extra burden for his grandfather, the Depression scarred Martin's faith in capitalism. His letters provide a unique insight into the complicated and ambiguous birth of a radical political consciousness. –Author's introduction
Keywords: Canada; DEPRESSIONS – 1929; Foreign workers; JOHANSSON; Martin; LABOR market; Labor movement; SOCIAL status; Working class